PERSEPSI IBU-IBU YANG PUNYA ANAK BALITA TERHADAP KINERJA KADER POSYANDU TERATAI DI DESA GADING SARI KECAMATAN TAPUNG KABUPATEN KAMPAR - Carnelita, Ineke; Maemunaty, Titi; Jas, Jaspar (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : This study aims to determine the perception of mothers who have children under five on the performance of Posyandu Posyandu cadre in the village of Gading Sari Tapung district Kampar regency. The formulation of the problem in this research is the perception of mothers who have children under five on the performance of Posyandu Posyandu cadre in the village of Gading Sari Tapung subdistrict, Kampar regency classified baik.Penelitian is also useful as a comparison material for other researchers who will conduct research in the same field, can then be used as material and information for Posyandu in order to improve the quality of public health service. This research is descriptive with quantitative approach which aims to describe the result of research with numbers. The sampling technique uses a saturated sampling technique. Data collection techniques in this study is a questionnaire that amounted to 40 items statement. Data were obtained from respondents who numbered 20 people for sample test and 50 for sample research. After the test questionnaire, there are 3 invalid items that are 7, 13 and 33 and the researcher discards the 3 invalid statements. The results of data analysis showed that the perception of mothers who have children under five on the performance of Posyandu Posyandu cadre in the village of Gading Sari Tapung subdistrict Kampar regency classified as good with an average percentage score of 79.916%. This means that the perception of mothers who have children under five to the performance of posyandu cadres in ivory sari village have a good perception level. In view of all aspects and can also be concluded that the most dominant is on Table 3 Listing.Keywords: Perception, Performance of Cadres, Posyandu